Pengaruh Penerapan Green Accounting dan Kinerja Lingkungan Terhadap Kinerja Keuangan - Fahira, Ainun; Mahsuni, Abdul Wahid; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine and analyze the effect of implementing green accounting and environmental performance on the financial performance of case studies in manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sample used was a purposive sampling method. The data collection method used in this research is the documentation technique for annual reports and sustainability reports of manufacturing companies listed on the Indonesian Stock Exchange from 2020 to 2022. Based on the results of research and testing conducted regarding the influence of green accounting, environmental performance on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange using SPSS 25.0, it can be concluded as follows: 1) Green accounting has no effect on the financial performance of manufacturing companies listed on Indonesian Stock Exchange for the 2020-2022 period. 2) Environmental performance has no effect on the financial.Keywords: Effect of implementation, green accounting, environmental performance, on financial performance.